The main factors influencing the formation of post-stress disorders in the population in the context of the current war in Ukraine - Pidkorytov, Валерій; Skrynnyk, Ольга; Serikova, Ольга; Serikov, Сергій (Psychosomatic Medicine and General Practice, 2024)
This text is the abstract of the report to the III Scientific and Practical Conference with International Participation "Psychiatry, Narcology, Clinical Psychology and General Medical Practice: Interdisciplinary Issues of the Present", March 22-23, 2024, Kyiv - online.